2011
DOI: 10.1111/j.1476-5381.2010.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin alleviates interstitial fibrosis and cardiac dysfunction of infarct rats by inhibiting TGFβ1 expression and activation of p38‐MAPK and ERK1/2

Abstract: BACKGROUND AND PURPOSE Interstitial fibrosis plays a causal role in the development of heart failure after chronic myocardial infarction (MI), and anti‐fibrotic therapy represents a promising strategy to mitigate this pathological process. The purpose of this study was to investigate the effect of long‐term administration of scutellarin (Scu) on cardiac interstitial fibrosis of myocardial infarct rats and the underlying mechanisms. EXPERIMENTAL APPROACH Scu was administered to rats that were subjected to coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 41 publications
4
63
0
Order By: Relevance
“…Fibronectin 1 may be induced by different agents including angiotensin II [59] and aldosterone [44]. Both of these stimuli may lead to vascular remodeling and vascular inflammation [44, 60].…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin 1 may be induced by different agents including angiotensin II [59] and aldosterone [44]. Both of these stimuli may lead to vascular remodeling and vascular inflammation [44, 60].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that p38 MAPK is involved in the regulation of myocyte contractile dysfunction, apoptosis andcell death in heart diseases. Many studies have demonstrated that inhibition of p38 MAPK reduced infarct size, attenuated myocardial fibrosis and improved heart function [40,41]. Recently, Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have also indicated that breviscapine ameliorated the cardiac hypertrophy that was induced by high glucose in diabetic rats through inhibiting the PKC signaling pathway [16,17] . Other studies have demonstrated that breviscapine inhibited the proliferation and collagen production by cardiac fibroblasts that were induced by angiotensin II through the suppression of the p38 and ERK1/2 MAPK signaling pathways [18] . In addition, breviscapine has been shown to potentially have a protective effect against atherosclerosis in rats [19] .…”
Section: Introductionmentioning
confidence: 99%